Quadrennial Defense Review 2014: Trends in US defense policy and consequences for NATO - Marco Overhaus (Stiftung Wissenschaft und Politik (SWP), 2014)
Every four years the Pentagon publishes a report on the central developments and trends in US defense policy. The Quadrennial Defense Review (QDR) released in early March 2014 is the first to include in more detail the consequences of the defense budget cuts passed since 2011. Otherwise, the so-called US rebalance to the Asia-Pacific region and the war-weariness of the American people are the principal factors shaping US defense policy. While not representing a watershed for transatlantic defense cooperation, the trends outlined in the QDR do contain risks and potential for conflict in the relationship with Europe. (SWP Comments)
Keywords: 320